Intraspecific variation of Centruroides Edwardsii venom from two regions of Colombia (2014)
We report the first description studies, partial characterization, and intraspecific difference of Centruroides edwardsii, Gervais 1843, venom. C. edwardsii from two Colombian regions (Antioquia and Tolima) were evaluated. Both venoms showed hemolytic activity, possibly dependent of enzymatic active phospholipases, and neither coagulant nor proteolytic activities were observed. Venom electrophoretic profile showed significant differences between C. edwardsii venom from both regions. A high concentration of proteins with molecular masses between 31 kDa and 97.4 kDa, and an important concentration close or below 14.4 kDa were detected. RP-HPLC retention times between 38.2 min and 42.1 min, showed bands close to 14.4 kDa, which may correspond to phospholipases. RP-HPLC venom profile showed a well conserved region in both venoms between 7 and 17 min, after this, significant differences were detected. From Tolima region venom, 50 well-defined peaks were detected, while in the Antioquia region venom, 55 well-defined peaks were detected. Larvicidal activity was only detected in the C. edwardsii venom from Antioquia. No antimicrobial activity was observed using complete venom or RP-HPLC collected fractions of both venoms. Lethally activity (carried out on female albino swiss mice) was detected at doses over 19.2 mg/kg of crude venom. Toxic effects included distress, excitability, eye irritation and secretions, hyperventilation, ataxia, paralysis, and salivation. © 2014 by the authors; licensee MDPI, Basel, Switzerland.